CHALLENGES FACING THE EHLANZENI DISTRICT MUNICIPALITY IN THE IMPLEMENTATION OF LOCAL ECONOMIC DEVELOPMENT PROGRAMME - MAHLALELA, NONTOBEKO PORTIA (My University, 2011)
This research project employs case study methodology to explore the factors that impact on Ehlanzeni District Municipality‟s efforts to implement local economic development (LED) interventions to improve the livelihoods of poor communities. More specifically, the goal of this thesis is to explore some of the reasons why LED interventions often struggle to meet their main objective of improving the livelihoods of local poor people. It is hoped that the findings of this research will assist policymakers and local economic development planners in making more informed decisions. In conclusion, it is argued that while the potential LED is not disputed, the implementation of such strategies are often inconsistent with the overall objective of poverty alleviation and economic development. For this reason, local municipalities will not be able to do this without clear policy guidance; institutional capacity-building; inter-sectoral collaboration of political „champions‟ to drive the process; and real empowerment of the beneficiaries whom the projects are supposed to assist.
MM thesis - P&DM
Keywords: Economic development programmes; Local authorities; Municipalities